Rekrutmen, Motivasi dan Kompetensi Terhadap Kinerja Karyawan pada PDAM Bondowoso - Ismi Azizah; Trias Setyowati; Tatit Diansari R (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aims to determine the effect of recruitment, motivation and competency analysis on employee performance at Pdam Bondowoso. This research method is quantitative. Data collection techniques using observation, interviews and questionnaires to 98 respondents with census techniques. The analytical tools used in this research are validity test, religious test, classical assumption test, linear regression analysis, t test, and r2 test. The results of the study show, a) recruitment has an effect on the performance of PDAM Bondowoso employees. With a significance level of 0.04 0.05 (value); b) there is a positive and significant effect between motivation on organizational performance with a significance level of 0.00. < 0.05 (a value); c) there is a positive and significant influence between competence and employee performance with a significance level of 0.04 0.05 (values ​​of X2 and x3); d) jointly have a positive and significant effect on organizational performance on permanent employees of the Bondowoso Regency PDAM office. In conclusion, recruitment, motivation, and competence have a significant effect on the performance of PDAM Bondowoso employees. Keywords: Employee Performance, Competence, Motivation, Recruitment